Institutional role in the management of Pela tourism village, Kota Bangun district, Kutai Kartanegara regency, East Kalimantan - Hattori, Eron Alfon; Sibarani, Putra Adrian; Khairi, Nurhafizah (Journal of Commerce, Management, and Tourism Studies, 2023)
Tourism villages offer a unique attraction that involves the active participation of the local community in managing and promoting the tourism potential around them. However, to achieve success in developing tourism destinations in villages, it is important to understand the role of institutions in managing the governance of these destinations. From this, the authors are interested in conducting research with the title Institutional Role in Management located in Pela tourism village, Kota Bangun district, Kutai Kartanegara, East Kalimantan. This study aims to analyze the role of institutions in managing destinations in Pela Tourism Village. This study uses a qualitative method with data collection techniques of interviews and observations conducted in the village. The results of this study are that the institution has a role in managing tourism, empowering local communities to be actively involved in tourism activities, and involved in tourism development.